Music and gesture - Gritten, Anthony; King, Elaine (Hampshire Ashgate, 2006)
This volume showcases key theoretical ideas and practical considerations in the growing area of scholarship on musical gesture. The book constructs and explores the relations between music and gesture from a range of differing perspectives, identifying theoretical approaches and examining the nature of certain types of gesture in musical performance. The twelve chapters in this volume are organized into a heuristic progression from theory to practice, from essay to case study. Theoretical considerations about the interpretation of musical gestures are identified and phrased in terms of semiotics, the mimetic hypothesis, concepts of musical force, immanence, quotation and topic, and the work of musical gestures. The lives of musical gestures in performance are revealed through engaging with their rhythmic properties as well as inquiring into the breathing of pianists, the nature of clarinettists' bodily movements, and the physical acts and personae of individual artists, specifically Keith Jarrett and Robbie Williams. The reader is encouraged to listen to the various resonances and tensions between the chapters, including the importance given to bodies, processes, motions, expressions, and interpretations of musical gesture. The book will be of significance to musicologists, theorists, semioticians, analysts, composers and performers, as well as scholars working in different research communities with an interest in the study of gesture.